2016
DOI: 10.14257/ijfgcn.2016.9.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Research on Innovation of Physical Education Teaching Method based on Inquiry Teaching: A Survey based on Online Questionnaire

Abstract: In recent years, with the infiltration of new ideas in physical education

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…The questionnaire focused on three main aspects: The second aspect was measuring the AI-driven inquiry teaching method. Based on the research conducted by Shore [23] and Zhang [24], 4, 5, 5, and 4 measurement questions were proposed based on aspects of inquiry-based teaching: questioning, evidence acquisition, explanation focusing, and evaluation summary. The third aspect was measuring learning outcomes.…”
Section: Questionnaire Designmentioning
confidence: 99%
“…The questionnaire focused on three main aspects: The second aspect was measuring the AI-driven inquiry teaching method. Based on the research conducted by Shore [23] and Zhang [24], 4, 5, 5, and 4 measurement questions were proposed based on aspects of inquiry-based teaching: questioning, evidence acquisition, explanation focusing, and evaluation summary. The third aspect was measuring learning outcomes.…”
Section: Questionnaire Designmentioning
confidence: 99%
“…The literature review found plentiful theoretical studies that highlight the approaches to developing the healthy lifestyle behaviours in the students (Bakouei et al, 2019;Caliskan et al, 2018;Celebi et al, 2017;Kabakci, 2019). Pedagogical literature mostly focuses on pedagogical strategies targeting the physical activity or social skills of the students and schoolchildren aimed at establishing the environment that favours their successful learning and life enjoyment (Dudley, 2011;Lander et al, 2019;Ningthoujam et al, 2017;Syarifuddin et al, 2020;Zhang, 2016). Medical sources reveal the practice of health literacy promotion through running information campaigns and individual counselling (Almutairi, et al, 2018;Hadden, 2015;Juvinyа-Canal, et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other research, despite PE teachers' use of an FL model to introduce students to the rules of unfamiliar games (Bergmann & Sams, 2014), evidence of the model's impact remains unclear, as does its effects. Nevertheless, in general, researchers have called for more innovative teaching methods in PE (Zhang, 2016), and FL continues to rank among the possible responses (Zainuddin & Halili, 2016;Østerlie, 2016).…”
Section: Flipped Learning In Physical Educationmentioning
confidence: 99%